Pre-prticipation injury and illness complaints of elite athletes participating at the Munich 2022 European championships - Edouard, P.; Dandrieux, P.-E.; Hollander, K.; Zyskowski, M. (Deutsche Zeitschrift für Sportmedizin, 2023)
Objective: To describe the injury and illness complaints of elite athletes during the four weeks before the 2022 European championships in Munich (Germany).